ON THE STATISTICAL CONTROL OF THE RACING PROCESS BRACKET CENTER SUPPORT USING THE SIGMA SIX METHOD - Ancuţa BĂLTEANU; Monica BÂLDEA; Mihaela ISTRATE (Fiabilitate şi Durabilitate)
By applying the Six Sigma method, it is intended to calculate the capability reinforcement bracket support bracket process to see if it is stable and to see if the degree of dispersion of values is close to the limits of a normal distribution